How VC Background and Timing of Entry Become a Booster to Corporate Innovation:The Impact Path of the Capitalization of R&D Expenditure - Li, Xiaoyun (Transactions on Economics, Business and Management Research, 2024)
Venture capital background and entry timing affect the innovation behavior of firms is widely recognized. Based on the data of A-share listed companies from 2012 to 2021, this paper finds that venture capital with foreign investment background plays a more significant role in improving the innovation performance of firms. Venture capital in the initial stage and development stage can promote firm innovation to a certain extent, and the venture capital entered in the expansion period will inhibit the innovation of firms. When venture capital has the background of foreign capital or enters in the development period, the capitalization of R&D expenditure plays a partial intermediary role between venture capital and firm innovation. To improve innovation performance, it is necessary to reasonably introduce foreign capital, encourage venture capital to enter in the development period of firms, and give full play to the positive signal role of capitalization of firm R&D expenditure.